(untitled) (مجلة المنصور, 2022)
The present paper sheds light on the interdependent relation between compounding and pragmatics. Different approaches to analyze compounds are examined .These are descriptive, semantic, typological, generativist, and pragmatic ;all confirmed that the set of compounding semantic relations is infinite. The reference to pragmatic information is crucial , since it leads both the speaker and hearer to question if compound interpretation can be formalized at all. The most important problems in any pragmatic theory to compounding are redundant compounds , indirect compounding relations , and lack of generalization. Pragmatics and extralinguistic knowledge help the speaker and the listener reduce multiple ambiguities and inherent vagueness of these compound forms in ways that a purely grammatical/semantic description does not. Pragmatic theories stress the importance of context in compound interpretation , social , cultural and stylistic background of the speaker and hearer.